Plan de negocio para el lanzamiento de un servicio de organización integral de bodas de destino en Perú - Varese, Carmela (2023)
The purpose of presenting this thesis is to investigate and set up a wedding planning company, entering a new market niche that has been developing internationally for more than 20 years and that in Peru is practically a market virgin as destination weddings are. What is sought is to develop a wedding planning company based in Lima that allows weddings to be organized in any destination outside the headquarters nationwide, providing a personalized and comprehensive service. Basically, the idea is to venture into the Romance Tourism Industry by creating a company that meets each and every one of the requirements that an international client request. After creating the company, we will plan a destination wedding designed outside the capital where we can verify its viability and identify the challenges that every Wedding Planner must take into account when offering this type of service nationally and internationally.